Histological Features Detected for Separation of the Edible Leaves of Allium ursinum L. from the Poisonous Leaves of Convallaria majalis L. and Colchicum autumnale L. - Márta M-Hamvas; Angéla Tótik; Csongor Freytag; Attila Gáspár; Amina Nouar; Tamás Garda; Csaba Máthé (Plants)
Allium ursinum (wild garlic) has long been collected and consumed as food and medicine in the north temperate zone, where its popularity is growing. Colchicum autumnale and Convallaria majalis contain toxic alkaloids. Their habitats overlap, and without flowers, their vegetative organs are similar. Confusing the leaves of Colchicum or Convallaria with the leaves of wild garlic has repeatedly led to serious human and animal poisonings. Our goal was to find a histological characteristic that makes the separation of these leaves clear. We compared the anatomy of foliage leaves of these three species grown in the same garden (Debrecen, Hungary, Central Europe). We used a bright-field microscope to characterize the transversal sections of leaves. Cell types of epidermises were compared based on peels and different impressions. We established some significant differences in the histology of leaves. The adaxial peels of Allium consist of only “long” cells without stomata, but the abaxial ones show “long”, “short” and “T” cells with wavy cell walls as a peculiarity, and stomata. Convallaria and Colchicum leaves are amphystomatic, but in the case of Allium, they are hypostomatic. These traits were confirmed with herbarium specimens. Our results help to clearly identify these species even in mixed, dried plant material and may be used for diagnostic purposes.